Burden of Seizure Clusters on Patients With Epilepsy and Caregivers: Survey of Patient, Caregiver, and Clinician Perspectives. Issue 6 (November 2017) - Penovich, Patricia E.; Buelow, Janice; Steinberg, Kathy; Sirven, Joseph; Wheless, James
Abstract : Objectives: To characterize the burden of seizure clusters (SC) on patients and caregivers, a large internet-based survey was conducted. Methods: The Seizure Cluster Burden of Illness US Survey was conducted online by Harris Poll on behalf of The Epilepsy Foundation in September 2014. Respondents included adult patients 18 years and above with epilepsy or a seizure disorder who had experienced SC in the past year (defined as ≥2 seizures within 24 h outside the patient's typical seizure pattern), caregivers providing current care for a patient with SC (adult or child), and clinicians (neurologists, epileptologists) who treat adult or pediatric patients. Responses to a wide range of topics, including emotional well-being, daily function, productivity, and approach to clinical practice, were collected. Results: There were 861 respondents (259 adult SC patients, 263 caregivers, and 339 clinicians). A majority of all respondent groups felt SC have a moderate/major negative impact on patient and caregiver quality of life, including emotional, financial, and social components. Responses indicated possible overutilization of emergency room services and underutilization of rescue treatment. Only 30% of patients reported having a seizure emergency plan. Some responses showed discrepancies between clinicians and patients/caregivers in the perceived degree of negative impact of SC and management practices for SC. Conclusions: These results suggest the need for increased education on managing SC. Clinicians need to develop seizure emergency plans and discuss rescue therapies, whereas patients and caregivers need to ask for and utilize these management strategies. Abstract : Supplemental Digital Content is available in the text.